Eksistensi Partai Politik Dalam Persepsi Publik [The Existence of The Political Parties in Public Perception] - NFN Efriza (Jurnal Politica, 2019)
A democratic country needs political parties. They become the driving force in the implementation of democracy in Indonesia considering the important role that they play in various political processes in the legislature, government, and other state institutions. Given the importance of political parties in Indonesia in the Reform era, it turns out that most problems come from political parties. This paper aims to gain an understanding of the development and role of political parties in the Reform era based on the public perception of the existence of political parties. Based on the objective of the study, the significance of this study can hopefully be elicited, which is to provide an understanding and an input on the development and role of political parties in the Reform era. Results of the study suggests that public perception of the performance of political parties as political infrastructure was still poor and that political parties were also responsible for the poor performance of the political superstructure institutions. Therefore, the researcher recommends that political parties internally need to strengthen party institutionalization, while on the other hand, there needs to be an effort to simplify party systems in Indonesia. AbstrakSebuah negara demokratis membutuhkan adanya partai politik. Partai politik menjadi tulang punggung bagi berjalannya demokrasi di Indonesia, sebab peran penting dalam aneka proses politik di lembaga legislatif, pemerintahan, dan lembaga-lembaga negara lainnya tidak bisa dilepaskan dari partai politik. Mengingat pentingnya posisi partai politik di Indonesia pada era reformasi ini, malah ternyata letak permasalahan ada di partai politik. Penulisan ini memiliki tujuan untuk memperoleh pemahaman mengenai perkembangan dan peran partai politik di era reformasi berdasarkan persepsi masyarakat atas eksistensi partai politik. Dari tujuan itu diharapkan dapat dihasilkan kegunaan kajian ini, yakni memberikan pemahaman dan masukan terhadap perkembangan dan peran partai politik di era reformasi ini. Penulisan ini menemukan fakta bahwa persepsi publik atas kinerja partai politik sebagai infrastruktur politik masih buruk dan partai politik juga dianggap bertanggung jawab atas masih buruknya kinerja lembaga suprastruktur politik. Oleh karena itu, rekomendasi yang ditawarkan adalah partai politik secara internal perlu melakukan penguatan institusionalisasi partai, di sisi lain perlu adanya upaya penyederhanaan sistem kepartaian di Indonesia.